Bilayer Dielectrics for RRAM Devices. (20th July 2018) - Misra, Durgamadhab; Sultana, Sabiha; Jain, Barsha; Bhat, Navakanta; Tapily, Kandabara; Clark, Robert D.; Consiglio, Steven; Wajda, Cory S.; Leusink, Gert J.
Abstract : To implement low power and highly reliable resistive random-access memory (RRAM) devices, suitable multi-layer dielectric materials are required. This consists of a switching layer, the oxygen vacancy medium, to form the filament and an oxygen vacancy deficient layer, such as Al2 O3 to control the filament rupture. This work explores several different bilayer structures using different dielectrics, electrode materials and processing conditions to reduce power consumption during forming, set and reset operations and to enhance endurance with a large Roff /Ron value for RRAM application. Several transition metal dielectrics (HfAlO2 or HfZrO2 ) were used as the switching layer on a thin Al2 O3 . By comparing the forming voltage values, Roff /Ron values and both set and reset power consumption, optimized performance was derived.